Neutropenia and G-CSF in lymphoproliferative diseases. (1st May 2013) - Ria, Roberto; Reale, Antonia; Moschetta, Michele; Dammacco, Franco; Vacca, Angelo
<x xml:space="preserve">Abstract</x> Background: Chemotherapy-induced neutropenia is a major cause of morbidity and mortality. It frequently causes dose reductions or treatment delay, which can be prevented or treated by the administration of granulocyte-colony-stimulating factor (G-CSF). However, a better knowledge of the incidence, day of onset after therapy, and duration of neutropenia is essential to optimize the use of G-CSF. Design and methods: Six hundred and ninety-four patients from a single institution, affected by lympho-proliferative diseases, were retrospectively reviewed for the occurrence of grade 4 neutropenia and febrile neutropenia (FN). Duration of neutropenia and time of neutrophil nadir were also retrieved. The diagnoses included non-Hodgkin's lymphoma, Hodgkin's lymphoma, and multiple myeloma. Chemotherapy regimens were obviously different according to the diagnosis, disease stage, and first or subsequent lines of therapy. Results: No patient received G-CSF as primary prophylaxis. Median nadir did not significantly differ among patients treated with first or successive lines of therapy. The incidence of grade 4 neutropenia and FN ranged from 0 to 94%, depending on the chemotherapy regimen. Patients receiving a first-line chemotherapy regimen had a significantly lower incidence of febrile grade 4 neutropenia compared to patients treated with a second or subsequent line of therapy. The duration of grade 4 neutropenia was significantly longer in patients given second or subsequent lines. Conclusion: The results of this study could be useful to define the nadir onset in the hematologic setting in order to correctly tailor timing and duration of G-CSF prophylaxis and to assess the lowest fully effective dose.